A Computationally Economic Location Algorithm for Bistatic EVMS-MIMO Radar - Tingting Liu; Fangqing Wen; Junpeng Shi; Ziheng Gong; Hui Xu (IEEE Access, 2019)
In this paper, we investigated into the problem of target location in a bistatic multiple-input multiple-output (MIMO), whose transmit antennas and receive antennas are electromagnetic vector sensors (EMVS). Unlike the traditional linear scaler-sensor array, a linear EMVS array can offer two-diemensional (2D) direction estimation, thus a bistatic EMVS-MIMO radar provides (2D) direction-of-arrival and 2D direction-of-departure estimation. Besides, it is able to estimate 2D transmit/receive polarization angles of the targets. An propagator method (PM)-based estimator is proposed. Firstly, it estimate the propagator from the covariance matrix. The parameters are achieved via utilizing the estimation method of signal parameters via rotational invariance technique (ESPRIT) and the vector cross-product technique. The proposed estimator is computationally friendly since it does not involving eigendecomposition of high-dimensional data. Also, it may has similar (or even better) parameter estimation accuracy than the current EPSRIT-Like algorithm. Simulation results verify the effectiveness of the proposed PM estimator.